Smart Label Based on Red Cabbage Extract (Brassica oleracea) as an Indicator of Freshness of Tuna Fillets at Chiller Temperature - Deli Silvia; Anisah Nur Nabilah Ishaq; Wiwi Prastiwinarti (Jurnal FishtecH, 2021)
Tuna fillets are considered good media for the growth of microorganisms because it contains a high protein level. In order to determine the rottenness of the tuna fillet, smart packaging is needed. Research has been carried out on making smart labels based on red cabbage extract as an indicator of the freshness of tuna fillets at chiller temperatures. The purpose of this research was to find the best pH variation of red cabbage extract for use as a tuna fillet indicator label. The indicator labels were made with variations in pH 2, 5, 8, and 11. The tests conducted in this research including mean RGB labels, pH tests, and organoleptic tuna fillets. This research used a Completely Randomized Design (CRD) method which consists of two repetitions for each test. The test was carried out for 8 days and tested every 2 days. From this research, it was found that the pH 2 label was the best pH variation to monitor the freshness of tuna fillets. The color change of the label occurred on the 4th day when the mean RGB label pH 2 was 168.802 ± 1.093 and the pH of the tuna filet was 6.11 ± 0.16. The organoleptic score had exceeded the sensory limit on day 4 of all parameters with the appearance, smell, and texture scores being 3.8 ± 1.0, respectively; 4.6 ± 0.8; 4.8 ± 1.4. The pH 2 label was chosen since there was a color change from pink to purple when detecting spoilage in tuna fillets.